2017
DOI: 10.1182/blood-2016-09-742049
|View full text |Cite
|
Sign up to set email alerts
|

CML cells actively evade host immune surveillance through cytokine-mediated downregulation of MHC-II expression

Abstract: Key Points• MHC-II and its master regulator CIITA are downregulated in CML stem/ progenitor cells in a BCR-ABL kinase-independent manner. • JAK1/2 inhibition increased MHC-II expression, suggesting elevation of CML immunogenicity may provide a way to reduce CML persistence.Targeting the fusion oncoprotein BCR-ABL with tyrosine kinase inhibitors has significantly affected chronic myeloid leukemia (CML) treatment, transforming the life expectancy of patients; however the risk for relapse remains, due to persiste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(48 citation statements)
references
References 49 publications
1
47
0
Order By: Relevance
“…Blockade of the PD-1/PD-L1 interaction in combination with T-cell immunotherapy was able to trigger the loss of LSC, and prevent development of CML-like disease 96 . Our recent work has demonstrated that cytokine-mediated downregulation of MHC-II expression may be an alternative way that LSC evade immune surveillance -and treatment with ruxolitinib or interferon gamma (IFNγ) can reverse this effect in vitro and enhance proliferation of responder CD4 + CD69 + T cells in mixed lymphocyte reactions 97 . These examples represent exciting areas of research that could lead to new immune therapy-based therapeutic approaches.…”
Section: The Lsc Bone Marrow Microenvironmentmentioning
confidence: 99%
“…Blockade of the PD-1/PD-L1 interaction in combination with T-cell immunotherapy was able to trigger the loss of LSC, and prevent development of CML-like disease 96 . Our recent work has demonstrated that cytokine-mediated downregulation of MHC-II expression may be an alternative way that LSC evade immune surveillance -and treatment with ruxolitinib or interferon gamma (IFNγ) can reverse this effect in vitro and enhance proliferation of responder CD4 + CD69 + T cells in mixed lymphocyte reactions 97 . These examples represent exciting areas of research that could lead to new immune therapy-based therapeutic approaches.…”
Section: The Lsc Bone Marrow Microenvironmentmentioning
confidence: 99%
“…In addition to the well-known graft-versus-leukemia effect of allo-SCT, other features point to CML as an immune-sensitive disease. These characteristics include immune surveillance evasion after downregulation of MHC-II expression by CML cells (15), BCR-ABL fusion region peptides that elicit CML-specific T-cell responses (16), the potential for autologous dendritic cell vaccination, the role of natural killer (NK) cells (17), the anti-BCR-ABL efficacy of T-helper or cytotoxic T lymphocytes (18,19), and the restoration of immune control associated with programmed cell death-1 (PD-1) inhibition in molecular (RM3.0) or deep-response CML patients (20). Thus, CML is a candidate for new immunotherapies.…”
Section: Introductionmentioning
confidence: 99%
“…Along with T cells, the natural killer (NK) cell compartment plays an important role for relapse prevention, because NK cells are activated owing to the absence of self-HLA class I molecules on malignant cells. Reduced expression of HLA class II molecules has been observed in, for example, chronic myelogenous leukemia [24], Hodgkin lymphoma, aggressive B cell lymphomas [25,26], and relapsed leukemia in patients without genomic HLA loss [27,28]. Reduced expression of HLA class II molecules has been shown to promote leukemia relapse, which could be counterbalanced by IFN-g treatment to enhance HLA expression [29].…”
Section: Biology Of Relapsementioning
confidence: 99%